2017
DOI: 10.17707/agricultforest.63.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate Changes on Wheat Viruses Variability in Ukraine

Abstract: SUMMARYClimate change is closely related to the level of losses from plant diseases because the environment significantly affects plants, pathogens and their vectors. Monitoring of viral infections in agrocenoses is one of the priority measures to preserve the harvest. However, often symptoms of the adaptive response of plants caused by environmental abiotic factors like the symptoms caused by infectious agents. In this regard, there is a problem to identify the reasons of pathological symptoms on the plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In 2006-2009, epiphytoty of CMV on fi eld-grown purple conefl ower was registered in Ukraine [17,33]. Monitoring of the plantations showed that 75 % of the plants were with the symptoms of viral infection.…”
Section: Cucumber Mosaic Virus CMVmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006-2009, epiphytoty of CMV on fi eld-grown purple conefl ower was registered in Ukraine [17,33]. Monitoring of the plantations showed that 75 % of the plants were with the symptoms of viral infection.…”
Section: Cucumber Mosaic Virus CMVmentioning
confidence: 99%
“…E. purpurea infected by CMV, AMV and TMV in Bulgaria: A -spotting on the leaves; B -dwarfed leaves and stunting[4] Echinacea purpurea infected by CMV in Ukraine: on each photo at the left -healthy plant, at the right -virus infected plant[17,33] …”
mentioning
confidence: 99%
“…The beginning of the autumn season was influenced by a severe drought, which lasted until October. Climate changes associated with global warming are closely related to the level of losses from plant diseases because the environment significantly affects plants, pathogens and their vectors (Mishchenko et al, 2017). Such weather conditions are favorable for aphids' reproduction and CMV distribution.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, soil-borne wheat viruses have been reported throughout the world [ 3 ], but the damage they cause is very difficult to evaluate, due to similar symptomatology shared with few physiological stresses. Their spread and severity are also predicted to be increased by climatic change [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%